Growth and yield of late sown rice varieties under various nitrogen management practices: Nitrogen management in late-sown rice varieties - Venkatesh, Durgam; Tuti, Mangal Deep; Lakshman, K; Brajendra; Chandrasekhar, K (ORYZA-An International Journal of Rice, 2025)
Late sowing in rice cultivation reduces the effective growing window, adversely affecting crop performance and nitrogen use efficiency (NUE). Adopting short-duration varieties along with efficient nitrogen management practices can mitigate these effects. A field experiment was conducted during kharif 2021 at ICAR-Indian Institute of Rice Research, Hyderabad, to evaluate the performance of short-duration rice varieties under late-sown conditions and identify suitable nitrogen management strategies. The experiment was laid out in a split-plot design with three replications. The main plot treatments included three short-duration rice varieties: DRR Dhan-44, MTU 1010, and MTU 1156. The subplot treatments comprised four nitrogen management strategies: recommended dose of nitrogen (RDN) @ 120 kg N ha-1, slow-release silicon-coated urea (SRSCU) @ 90 kg N ha-1, Leaf Colour Chart (LCC)-based application @ 105 kg N ha-1, and Soil Test Crop Response (STCR)-based application @ 114.5 kg N ha-1. Among the varieties, MTU 1156 recorded the highest grain yield (5.71 t ha-1), dry matter accumulation (12.43 t ha-1), leaf area index (4.12), and productive tillers (285 m-²). Among nitrogen treatments, LCC-based application @ 105 kg N ha-1 resulted in the highest grain yield (5.76 t ha-1) and was statistically at par with RDN. SRSCU recorded the lowest yield. The highest partial factor productivity of N (PFPN), was observed in MTU 1156 (55 kg grain kg-1 N). The study concludes that MTU 1156 combined with LCC-based nitrogen management is an effective strategy for sustaining rice productivity under late-sown conditions.